Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 month ago

Can someone please solve this equation step by step. Thank you!?

7(s-5)=42

Update:

THANK YOU to all of you who helped!

9 Answers

Relevance
  • 1 month ago

    7(s - 5) = 4 

    Multiply out the brackets 

    7s - 35 = 42 

    Add '35' to both sides 

    7s = 77 

    Divide both sides by '7' 

    s = 11 

    The answer !!!!!

    • Commenter avatarLogin to reply the answers
  • 1 month ago

    7(s-5)=42

    7s-35=42

    7s=42-35

    7s=7

    s=1

    • Commenter avatarLogin to reply the answers
  • RR
    Lv 7
    1 month ago

    7(s-5)=42

    multiply out the bracket

    7s - 35 = 42

    swap - 35 to other side

    7s = 77

    Divide 7 into 77

    s = 11

    • Commenter avatarLogin to reply the answers
  • 1 month ago

    7(s - 5) = 42

    7(s - 5)/7 = 42/7

    s - 5 = 6

    s - 5 + 5 = 6 + 5

    s = 11

    • Commenter avatarLogin to reply the answers
  • How do you think about the answers? You can sign in to vote the answer.
  • Ray S
    Lv 7
    1 month ago

    ➊  7(s-5) = 42        ← On the left, we have the product of the two numbers 7 and (s-5).  

                                       So, we can divide both sides by 7 to isolate the number involving s.

        7(s-5)       42

      ——— = ——

           7           7

    ➋  (s - 5) = 6          ← The parentheses no longer serve a purpose. 

                                        So, we can remove them.

                                        Then, to get s by itself, we need to add 5 to the left side.

                                        And, add 5 to the right side to keep the equation balanced.

      s - 5 + 5 = 6 + 5

            s + 0 = 11

    ➌           s = 11         ← ANSWER ... Steps ➊, ➋, and ➌ are all you should need to show.

    • Commenter avatarLogin to reply the answers
  • Philip
    Lv 6
    1 month ago

    7(s-5) = 42. The objective is to isolate s on one side of the equation. Then we can say ''s = ...whatever'' giving the correct answer. In our case we can do this in 2 easy

    steps. Step1: Divide equation through by 7 getting s-5 = 6..(1), Step2: Add 5 to both

    sides of equation in (1) getting s = 6+5. Then s = 11.

    • Commenter avatarLogin to reply the answers
  • 1 month ago

    7(s - 5) = 42

    s - 5 = 6

    s = 11

    • Commenter avatarLogin to reply the answers
  • david
    Lv 7
    1 month ago

    divide by 7

      s - 5  =  6   ...  now add 5

       s = 11  <<<  answer

     

    • Commenter avatarLogin to reply the answers
  • TomV
    Lv 7
    1 month ago

    7(s-5)=42

    Divide by 7

    s - 5 = 6

    Add 5

    s = 11

    • Commenter avatarLogin to reply the answers
Still have questions? Get your answers by asking now.